Adolescentes infractores en el Ecuador - Rosero, Verónica G. (2020)
Ecuador is a country that watches over the well-being of children and adolescents (NNA) therefore its juvenile justice system exercises a restorative approach that has as its objective to hold the offender responsible for his crime, through the recognition and reparation to the victim. The centers for adolescent offenders in the country carry out a comprehensive intervention with the expectation of obtaining positive changes and thus favoring the reintegration of this population into society. In general, it is considered that adolescents who are in conflict with the law correspond to a group of large vulnerability due to being immersed in risks such as violence, abandonment, absenteeism school, child exploitation, prostitution, dependence on psychoactive substances among others. Criminal responsibility is a topic of great debate in recent years and in At present, it is known that the adolescent is a subject of law, therefore, the Ecuadorian legislation made changes to its regulations and policies to exercise rights and obligations of the minor in order to guarantee the interest top of the NNA. The purpose of this degree work is to give understand risk and protective factors, review historical data, and statistics of the legal regulations of the juvenile justice system, its models, and the protocols and intervention programs applied in Ecuador.